A Quantitative Study of Demographic Effect on Purchase Decision of Online Nepalese Consumers - Bhandari, Kanchan; Paudel, Sajita; Ghimire, Shiva Lal; Acharya, Bhumi Raj (International Journal of Atharva, 2026)
Background: Nepal’s rapidly expanding digital landscape, driven by increased mobile broadband and smartphone affordability, has created a fertile ground for e-commerce growth. While young, educated, urban consumers dominate online shopping, a clear gap exists in understanding how demographic factors like age, gender, and education systematically influence specific stages of the online purchase decision within this evolving context. Objectives: This study aims to analyze the influence of age, gender, and education level on the purchase decisions of Nepalese online consumers, focusing on consumer choice factors, personal buying habits, and expectations for a seamless online experience. Methods: A quantitative, cross-sectional research design was employed. Data were collected from 384 online shoppers in the Kathmandu Valley using a structured questionnaire. Descriptive statistics and regression analysis were used to analyze the demographic effects. Findings: Age emerged as the most significant and consistent predictor of online purchase behavior, positively influencing consumer choice factors and buying habits. Gender showed a significant but context-specific effect, particularly on personal buying habits, while education level did not demonstrate a statistically significant influence on any of the analyzed behavioral dimensions. Conclusion: Demographic factors, especially age, play a significant but nuanced role in shaping online consumer behavior in Nepal. The non-significant influence of education suggests a democratization of e-commerce engagement, likely due to widespread smartphone use. E-commerce platforms should develop age-sensitive strategies and user-friendly interfaces. Novelty: This study provides a focused, quantitative analysis of how demographic variables distinctly affect multiple dimensions of the online purchase decision in Nepal’s contemporary, rapidly digitizing market.